2011
DOI: 10.1038/jid.2011.110
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens-Associated 1 Contributes to Cortactin Deacetylation and Augments the Migration of Melanoma Cells

Abstract: We investigated the prognostic significance and post-transcriptional acetylation-modification of cortactin (CTTN) via the nucleus accumbens-associated 1 (NACC1)-histone deacetylase 6 (HDAC6) deacetylation system in primary melanomas and melanoma cell lines. Overexpression of CTTN protein was observed in 56 (73%) of 77 stage I-IV melanomas, and was significantly correlated with tumor thickness, lymph node metastasis, distant metastasis, and disease outcome. The patients whose tumors exhibited CTTN overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…We recently reported that disruption of HDAC6 was closely associated with a decease of in vitro migration and invasion activities of melanoma cells (22). Inactivation of HDAC6 induced hyperacetylation of not only TUBA1 (13) but also CTTN (22). It introduced stabilization of MT dynamicity, and prevented the translocation of cortactin protein to the cell periphery, thus blocking its association with F-actin, and impairing the motility of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently reported that disruption of HDAC6 was closely associated with a decease of in vitro migration and invasion activities of melanoma cells (22). Inactivation of HDAC6 induced hyperacetylation of not only TUBA1 (13) but also CTTN (22). It introduced stabilization of MT dynamicity, and prevented the translocation of cortactin protein to the cell periphery, thus blocking its association with F-actin, and impairing the motility of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that disruption of HDAC6 was closely associated with a decease of in vitro migration and invasion activities of melanoma cells (22). Inactivation of HDAC6 induced hyperacetylation of not only TUBA1 (13) but also CTTN (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, only five karyometric features descriptive of the nuclear chromatin distribution provided a recognition of more than 70% of patients who might benefit from intensive therapy. The karyometric features relate to subtle changes in the spatial and statistical distribution of the nuclear chromatin, suggesting not only histone modification but also cellular aggression [20].…”
Section: Discussionmentioning
confidence: 99%